Effectiveness of Repetitive Transcranial Magnetic Stimulation for Improving the Verbal Memory of Patients with Anomic Aphasia in South Korea - Byeon, Haewon; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: The objective of the present research was to evaluate the effects of the repetitive transcranial magnetic stimulation (rTMS) application to the patients with anomic aphasia on the verbal memory (VM).Methods/Statistical analysis: This study was conducted on 31 patients, who were diagnosed with anomic aphasia due to the stroke. Subjects were randomly divided into a treatment group (receiving rTMS; n=16) and a control group (Sham TMS; n=15). The location of the rTMS stimulus was the left dorsolateral prefrontal cortex (DLPFC) and the 1Hz TMS was given 20 minutes per time and three times per week for four weeks. The positions of the electrodes of the Sham TMS group were identical to those of the treatment group and the stimulation stopped 30 seconds after the application.Verbal memory evaluation was conducted by using the Korean version of the Consortium to Establish a Registry of Alzheimer's Disease assessment battery (CERAD-K).Findings: The results of the ANCOVA indicated that there were significant differences (p <0.05) between the two groups in immediate verbal memory (IVM), recognition verbal memory (RVM), and delayed verbal memory (DVM). The results of parameter estimation showed that IVM, RVM, and DVM were significantly higher in the treatment group by 1.9, 2.0, and 2.1, respectively, than in the control group.Improvements/Applications: The results of this study suggested that the repeated stimulation on the left dorsolateral prefrontal cortex using the rTMS could improve the VM of stroke patients.